Keluarga Berencana Perspektif Ulama Hadis - Emilia Sari (SALAM: Jurnal Sosial dan Budaya Syar-i, 2019)
Abstract:Family planning is a slogan in the modern era that dictates community members to plan the number of children to be born in a household. For this reason, pregnancy prevention is carried out with this family planning program. This program is carried out with medical technology tools that are modern and traditional. In the study of Islamic jurisprudence itself, there has been a way to prevent pregnancy behavior by way of Azl, even though it has drawn controversy and differences in views from the jurists. This behavior is considered by some experts as natural family behavior that is permissible. Further discussion will be explained in this paper.Keywords: Family Planning, Hadith, Law Abstrak: Keluarga berencana merupakan suatu slogan di era modern yang mendoktrin anggota masyarakat untuk melakukan perencanaan jumlah anak yang akan dilahirkan dalam suatu rumah tangga. Untuk itu dilakukan penanggulangan kehamilan dengan Program KB ini. Program ini dilakukan dengan alat teknologi kedokteran yang modern maupun dengan cara tradisional. Dalam kajian fiqih Islam sendiri pernah terjadi bagaimana perilaku pencegahan kehamilan dengan cara Azl, walaupun hal tersebut menuai kontroversi dan perbedaan pandangan dari para ahli fikih. Perilaku ini dianggap oleh sebagian ahli sebagai perilaku KB alami yang dibolehkan. Pembahasan lebih lanjut akan dijelaskan dalam makalah ini.Kata Kunci: Keluarga Berencana, Hadis, Hukum